Control of passion fruit diseases : current status and perspectves - Peruch, Luiz Augusto Martins (2018)
Abstract: Phytosanitary control of diseases can be considered a crucial factor in the production of passion fruit. The chemical control associated to cultural and genetic approaches, may be the best way to reduce the losses caused by the fungal, bacterial and viral diseases of this fruit. There are several protective and systemic fungicides available for the chemical control, especially triazoles and strobilurins formulations. Recommended cultural control practices would be a balanced fertilization, destruction of cultural remains, adoption of windbreaks, etc. In a future perspective, the availability of resistant cultivars adapted to the different regions of Brazil will be important.